Pengaruh Pengetahuan Pajak, Tingkat Kesadaran Wajib Pajak, Kualitas Pelayanan Dan Penerapan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Roda Dua (Studi Kasus Samsat Jakarta Timur) Tahun 2020-2023 - Shifa, Rizkia; Kumala, Ratih (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study aims to determine the effect of tax knowledge, the level of awareness of taxpayers, service quality, and the application of tax sanctions on the compliance of two-wheeled motorized vehicle taxpayers at the East Jakarta SAMSAT Office. This study uses quantitative methods and through distributing questionnaires to 100 respondents who are registered as two-wheeled motorized vehicle taxpayers at SAMSAT East Jakarta. The sample used is Sample Random Sampling. The data analysis technique uses multiple regression analysis. The results of this study indicate that tax knowledge has no positive and significant effect on taxpayer compliance by 28.1%. The level of taxpayer awareness has a positive and significant effect on taxpayer compliance by 37.7%. Service quality has a positive and significant effect on taxpayer compliance by 32.4% and the application of tax sanctions has no positive and significant effect on taxpayer compliance by 17.1%. Tax Knowledge, Taxpayer Awareness Level, Service Quality and Application of Tax Sanctions have a positive and significant effect on Taxpayer Compliance for Two Wheeled Motorized Vehicles by 44.6% while the remaining 66.4% is influenced by other factors not examined in this study